Energy analysis during biped walking - Silva, Filipe M. (1999)
This paper describes the dynamic analysis of biped locomotion systems. A planar biped is modelled and studied focusing on the problem of energy efficiency. First, the motion of the system is characterised in terms of a set of locomotion variables, namely: step length, hip heiht, hip ripple, hip offset, foot clearance and link lengths. Afterwards, three cost functions related to energy are proposed: absolute power, power dispersion and power lost. The aim is to understand the influence of these locomotion variables on the energy flow. The performance measure are discussed and the results compared with those observed in nature.